2011
DOI: 10.1021/jo200948x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Allylic Hydroperoxides and EPR Spin-Trapping Studies on the Formation of Radicals in Iron Systems as Potential Initiators of the Sensitizing Pathway

Abstract: Many terpenes used as fragrance compounds autoxidize when exposed to air, forming allylic hydroperoxides that have the potential to be skin contact allergens. To trigger the immunotoxicity process that characterizes contact allergy, these hydroperoxides are supposed to bind covalently to proteins in the skin via radical pathways. We investigated the formation of reactive radical intermediates from 7-hydroperoxy-3,7-dimethylocta-1,5-dien-3-ol and 2-hydroperoxylimonene, responsible for the sensitizing potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 60 publications
2
63
0
Order By: Relevance
“…29,30 For the mixture Citr-6/7-OOH, we used exactly the same procedure as described for Lin-6/7-OOH, and obtained, for both mixtures, an isomer ratio of 6:4. 30 Cyc-hex-OOH was also synthesized with a method described in the literature. 31 All synthesized compounds were pure according to the 1 H and 13 C nuclear magnetic resonance F I G U R E 1 Chemical structures of terpene hydroperoxides included in this study: limonene-1-hydroperoxide (1), limonene-2hydroperoxide (2), linalool-6-hydroperoxide (3), linalool-7hydroperoxide (4), citronellol-6-hydroperoxide (5), citronellol-7hydroperoxide (6), cumene hydroperoxide (7), and 1-(1-hydroperoxy-1-methylethyl)cyclohexene (8) characterizations, in agreement with the literature.…”
Section: Chemicalsmentioning
confidence: 99%
“…29,30 For the mixture Citr-6/7-OOH, we used exactly the same procedure as described for Lin-6/7-OOH, and obtained, for both mixtures, an isomer ratio of 6:4. 30 Cyc-hex-OOH was also synthesized with a method described in the literature. 31 All synthesized compounds were pure according to the 1 H and 13 C nuclear magnetic resonance F I G U R E 1 Chemical structures of terpene hydroperoxides included in this study: limonene-1-hydroperoxide (1), limonene-2hydroperoxide (2), linalool-6-hydroperoxide (3), linalool-7hydroperoxide (4), citronellol-6-hydroperoxide (5), citronellol-7hydroperoxide (6), cumene hydroperoxide (7), and 1-(1-hydroperoxy-1-methylethyl)cyclohexene (8) characterizations, in agreement with the literature.…”
Section: Chemicalsmentioning
confidence: 99%
“…A mixture of linalool hydroperoxide isomers was obtained by synthesis using the method of Kao et al as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…Preparations of purified limonene hydroperoxide isomers and linalool hydroperoxide isomers have been previously reported, so the corresponding PHAs should be obtained in situ by simply mixing them with a relevant aldehyde in a nonpolar solvent. The aldehydes endogenous to citrus oils, such as octanal and/or decanal, are relevant aldehydes for the purpose herein.…”
Section: Introductionmentioning
confidence: 99%
“…Skold et al had prepared a mixture of II and III via a Rose Bengal photosensitized oxidation of linalyl acetate, and characterized the hydroperoxide products by 1H and 13C NMR . Using their characterization data for structural confirmation purposes, we attempted to prepare a mixture of II and III via a chemical oxidation reported by Kao et al that had worked for linalool oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from linalyl acetate, we duplicated the Kao et al synthetic procedure to obtain linalyl acetate hydroperoxide (Figure ). We expected a product mixture containing two positional isomers as reported for linalool, but hoped that the corresponding acetates (II and III) would be separable by column chromatography.…”
Section: Introductionmentioning
confidence: 99%